The Effect of Iron Deficiency Anemia on HbA1C among Non-Diabetic Adults in Benghazi, Libya - F. Idris, Basma; Kaziri , Ibtisam; Suliman Meelad , Ghada; Mohamed Saad , Saad; Suliman Meelad , Tamim; H. A. Amer , Abeer (Scientific Journal of University of Benghazi, 2024)
Iron Deficiency Anemia (IDA) is the most common hematological disorder that has an impact on various physiological processes in the body. This research aims to investigate the relation between IDA and HbA1c levels, a marker of long-term glycemic control. Data from 100 patients with IDA and 100 as a control group were collected from the First Medical Tech Laboratory in Benghazi, Libya, and analyzed using SPSS version 21. The distribution of age and sex among the groups was described using frequency and summary statistics. The statistical analysis showed that the data follows a normal distribution. However, it was not homogenous. Consequently, the non-parametric Mann-Whitney U test was employed. The results indicated no statistically significant correlation between IDA and HbA1c levels (p = 0.08), suggesting that IDA may not have a significant impact on long-term glycemic control. These findings contribute to the existing body of literature on the relationship between IDA and HbA1c levels, and many researchers suggest the fact that IDA increases HbA1c levels; others align with our results by showing no correlation; some even suggest that IDA decreases HBA1c levels. These conflicting results highlight the need for further research to shed light on the underlying mechanisms involved.